Implementasi Strategi Pembelajaran Inkuiri Dalam Pembelajaran Al-Qur’an dan Hadis - Arlina Arlina; M. Rayhan Ramadhan; Fitra Khairon; Nur Hasanah; Khoirunnisa Simanungkalit (EduInovasi: Journal of Basic Educational Studies, 2023)
Learning strategies are very important for an educator to use when teaching. The use of learning strategies should be a part that must get the attention of educators / facilitators in every learning activity. Therefore, educators need to learn and even develop how to set learning strategies in order to effectively achieve learning objectives in the teaching and learning process in the classroom, one of which is the application of appropriate learning strategies.This study uses a qualitative method in the form of descriptive. Data collection methods include interview, observation and documentation methods. Researchers acting as participants and informants of this study were the Head of Curriculum, Al-Quran Hadith teacher, and several seventh grade students. For the sample technique using purposive sampling.The validity of the data is done by triangulation of sources. For data analysis using data reduction, data presentation, conclusion drawing/verification. Based on the results of interviews and observations that have been made by the researcher, it was found data stating that the application of the inquiry learning strategy includes lesson planning, implementation of learning strategies consisting of observation, formulating problems, analyzing hypotheses, analyzing data, and drawing conclusions. The last stage is the closing and evaluation stage. In addition, it was also found that there was a process of compiling problems using the question and answer method and when delivering conclusions using the lecture method. Keywords: Inquiry Learning Strategy, Quranic Learning Hadith